2021
DOI: 10.1063/5.0069633
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order exceptional point and Landau–Zener Bloch oscillations in driven non-Hermitian photonic Lieb lattices

Abstract: We propose a scheme to realize parity-time (PT) symmetric photonic Lieb lattices of ribbon shape and complex couplings, thereby demonstrating the higher-order exceptional point (EP) and Landau–Zener Bloch (LZB) oscillations in the presence of a refractive index gradient. Quite different from non-Hermitian flatband lattices with on-site gain/loss, which undergo thresholdless PT symmetry breaking, the spectrum for such quasi-one-dimensional Lieb lattices has completely real values when the index gradient is appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…For instance, a 2D PT-symmetry graphene lattice demonstrates the relation between the PT-symmetry phase transition and the topological phase transition [112] (Figure 4b,c); a PT-symmetric Lieb lattice with ribbon shape and complex couplings demonstrates the higher-order EP and Landau-Zener Bloch oscillations. [113] As mentioned earlier, breaking the z-reversal symmetry of waveguide arrays is another way to endow physical systems with topologically nontrivial phases. When generalizing the Floquet topological theory to non-Hermitian systems, the interplay of Floquet topological phases and non-Hermiticity leads to more exotic effects that have no counterpart in static or Hermitian systems.…”
Section: Non-hermitian Effect In the Topological Waveguide Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a 2D PT-symmetry graphene lattice demonstrates the relation between the PT-symmetry phase transition and the topological phase transition [112] (Figure 4b,c); a PT-symmetric Lieb lattice with ribbon shape and complex couplings demonstrates the higher-order EP and Landau-Zener Bloch oscillations. [113] As mentioned earlier, breaking the z-reversal symmetry of waveguide arrays is another way to endow physical systems with topologically nontrivial phases. When generalizing the Floquet topological theory to non-Hermitian systems, the interplay of Floquet topological phases and non-Hermiticity leads to more exotic effects that have no counterpart in static or Hermitian systems.…”
Section: Non-hermitian Effect In the Topological Waveguide Arraysmentioning
confidence: 99%
“…For instance, a 2D PT‐symmetry graphene lattice demonstrates the relation between the PT‐symmetry phase transition and the topological phase transition [ 112 ] (Figure 4b,c); a PT‐symmetric Lieb lattice with ribbon shape and complex couplings demonstrates the higher‐order EP and Landau–Zener Bloch oscillations. [ 113 ]…”
Section: Non‐hermitian Effect In the Topological Waveguide Arraysmentioning
confidence: 99%
“…For PT -symmetric systems, the dynamics of OTOCs signals the Yang-Lee edge singularity [28] of phase transition and shows the quantized response to external driven potential [29]. It is now widely accepted that the non-Hermiticity is a fundamental modification to conventional quantum mechanics [30][31][32][33][34][35][36] since many systems, such as optics propagation in the "gain-or-loss" medium [37][38][39], the electronics transport in the dissipative circuit [40][41][42][43], and cold atoms in the tailored magneto-optical trap [44][45][46][47][48], are described by a non-Hermitian theory. The extension of Floquet systems to non-Hermitian regimes uncovers rich understandings of physics [49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…It has shown that the PT -symmetric frustrated lattices with fine-tuned non-Hermitian couplings can also give arise to flatbands as well as EPs [31]. More importantly, recent progress has demonstrated that even the higherorder EPs can exist in the PT -symmetric flatband lat-tices [32][33][34]. Nevertheless, due to the band touching (vanishing bandgap) between flat and dispersive bands, so far, realizations of the non-zero valued higher-order EPs have been limited to flatband systems with non-Hermitian couplings [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%